Compact Narrow Linewidth Actively Q-Switched Er–Yb Double-Clad Fiber Laser - Posada Ramírez, Berenice; Durán Sánchez, Manuel; Alvarez Tamayo, Ricardo Iván; Alaniz Baylón, Jared; Salceda Delgado, Guillermo; Kuzin, Evgeny A.; Ibarra Escamilla, Baldemar (2017)
Abstract: Actively Q-switched laser operation of a narrow linewidth compact ﬁber laser based on an Er–Yb double-clad ﬁber is presented. The laser linewidth as a function of the repetition rate and the Q-switched pulses characteristics for different pump powers are experimentally analyzed. Stable Q-switched laser operation with spectral laser linewidth of 73 pm in a repetition rate range from 90 to 270 kHz is obtained. The minimum pulse duration of 178 ns, maximum peak power of 30.5 W, and maximum pulse energy of 5.4 µJ are observed. The maximum average power reached is 1.1 W. Keywords: ﬁber lasers; Q-switched lasers; Er–Yb double-clad ﬁber; ﬁber Bragg gratings